Website Design for the Sukarami Village Head's Office - Femi Mutiara; Ariansyah; Nur Aini Hutagalung (Yayasan Kita Menulis, 2026)
The Sukarami village head office is under the auspice of the village government which has an Organization structure the sukarami village head office is the village head office located in sukarami village,rambang district, muara enim regency, south Sumatra province.Currently, the sukarami village head office does not have a website so that everyone can find out about the village head office to find out information such as village profiles, history of village activities, village programs,village structures, infrastructure owned by the village, and information on social assistance from the government and regions.The purpose of this study is to build a website so that the community can more easily find out about what is in the sukarami village head office. The research method uses a descriptive qualitative method with data collection in the form of observation,interviews and literature studies.The type of data consists of qualitative data, and data sources consist of primary data and secondary data.The device development method uses the rapid application development method.The system design tools used are the care diagram class diagram the website uses the PHP and MySQL programming languages.